Influence of primary and secondary prevention indications on anxiety about the implantable cardioverter‐defibrillator. Issue 2 (19th November 2015) - Rahmawati, Anita; Chishaki, Akiko; Ohkusa, Tomoko; Sawatari, Hiroyuki; Tsuchihashi‐Makaya, Miyuki; Ohtsuka, Yuko; Nakai, Mori; Miyazono, Mami; Hashiguchi, Nobuko; Sakurada, Harumizu; Takemoto, Masao; Mukai, Yasushi; et al.
Abstract: Background: Implantable cardioverter‐defibrillators (ICDs) have been established for primary and secondary prevention of fatal arrhythmias. However, little is known about the influence of ICD indications on quality of life (QOL) and psychological disturbances. This study aimed to examine whether there were differences in QOL and psychological distress in patients that have an ICD for primary or secondary prevention of fatal arrhythmias. Methods: A multicenter survey of 179 consecutive outpatients (29.1% primary prevention) with ICD implantations completed the Short Form‐8 (SF‐8), Beck Depression Inventory (BDI), Impact of Event Scale‐Revised (IES‐R), State‐Trait Anxiety Inventory (STAI), and Worries about ICD (WAICD). Results: Patients with an ICD for primary prevention had a higher trait anxiety score and worries about ICD score than patients with an ICD for secondary prevention (41.7±12.4 vs. 34.7±12.3, p =0.001 and 39.6±18.0 vs. 30.0±18.9, p =0.002, respectively), even after adjusting for demographic and clinical characteristics. In multivariable analysis of variance, primary prevention ICD recipients reported a poorer QOL on the vitality subscale of the SF‐8. Conclusions: In our study population, which mostly consisted of New York Heart Association (NYHA) class I and II subjects, primary prevention ICD recipients were more prone to experience worries about their ICD, anxiety, and a poorer QOL compared to secondary prevention ICD recipients. In clinical practice, primary prevention ICD patients should be closely monitored. If warranted, they should be offered psychological intervention, as anxiety and low QOL were predictors of mortality.